Chemical Analysis of Burdock Root Constituents - Han, Zhiwu; Wang, Meizhi; Wang, Longyuan; Qu, Haijun; Li, Ping; Wang, Chunbo (Asian Journal of Chemistry, 2012)
An ethanolic solution of extracted burdock root was concentrated, suspended by water and extracted by petroleum ether, chloroform, ethyl acetate and n-butanol. Then, the solution was purified by silica gel, Sephadex LH-20 and C18 column chromatography to obtain 17 compounds. Nine structures of compounds, identified according to physical and chemical properties using IR, UV, ESIMS, 1H NMR, 13C NMR and other methods, include 3 petroleum ethers (b-sitosterol, oleanolic acid, ursolic acid), 4 chloroforms (b-sitosterol, daucosterol, syringaresinol, ethyl-b-D-pyran fruit glycosides), 1 ethyl acetate (1,5-O-two caffeoylquinic acid) and n-butanol parts (succinic acid and 5-hydroxy maltol). Oleanolic acid, ursolic acid, clove lignans, ethyl-b-D-pyran fruit glycoside, succinic acid and 5-hydroxy maltol were first isolated from burdock.